Towards a brighter tomorrow : the college barriers, hopes and plans of Black, Latino/a and Asian American students in California - Allen, Walter Recharde; Kimura-Walsh, Erin; Griffin, Kimberly A (Research on African American education., 2009)
The book aims to develop a clearer understanding of the influence of social dynamics on the educational opportunities of high school students of color in the urban setting of California's Los Angeles area. Specifically, we examine how students' backgrounds, high school experiences and own agency shape their college preparation processes and postsecondary aspirations. While some research has been done on high school students' college-choice process, this book is unique in its broad and comparative approach. It examines the experiences of students across 10 schools, identifying broad themes that are illustrated through specific case studies. This approach allows readers to understand the broader issues that face students from underserved backgrounds as they pursue college, while illuminating how these issues uniquely manifest hemselves in individual school contexts.